The troika host-pathogen-extrinsic factors in tuberculosis: modulating inflammation and clinical outcomes - Bastos, Hélder Novais (2018)
The Troika Host-Pathogen-Extrinsic Factors in Tuberculosis: Modulating Inflammation and Clinical Outcomes